2018
DOI: 10.2147/ott.s181062
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine inactivates NF-κB and potentiates the antitumor effects of gemcitabine on tongue cancer both in vitro and in vivo

Abstract: ObjectiveThe aim of this study was to investigate whether evodiamine (EVO) could potentiate the antitumor activity of gemcitabine (GEM) in tongue cancer cells and determine its potential underlying mechanisms.Materials and methodsHuman Tca8113 and CAL-27 tongue squamous carcinoma cell lines were treated with EVO and GEM in different sequences and doses, after which cell proliferation was measured. Drug interactions were analyzed using the Chou–Talalay method with CompuSyn software. Clonality, apoptosis, and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In the present study, the effective anticancer activity of Evo, which may be mediated by BMP9 via the upregulation of HIF-1α to partly increase the activity of p53, was demonstrated in human colon cancer. It has been reported that Evo exhibits great anti-cancer activities in many types of cancer, such as tongue, breast, colon, prostate and lung cancer (9)(10)(11)(12)26,27). As far as colon cancer is concerned, the anticancer activity of Evo may be mediated by inactivating the NF-κB (9) or TGF-β1 (11), or activating the p53/p21/Rb pathway (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the effective anticancer activity of Evo, which may be mediated by BMP9 via the upregulation of HIF-1α to partly increase the activity of p53, was demonstrated in human colon cancer. It has been reported that Evo exhibits great anti-cancer activities in many types of cancer, such as tongue, breast, colon, prostate and lung cancer (9)(10)(11)(12)26,27). As far as colon cancer is concerned, the anticancer activity of Evo may be mediated by inactivating the NF-κB (9) or TGF-β1 (11), or activating the p53/p21/Rb pathway (12).…”
Section: Discussionmentioning
confidence: 99%
“…Evodiamine (Evo), a quinolone alkaloid extracted from traditional herbal medicine Evodia rutaecarpa (7), has multiple pharmacological actions and could be used for obesity, inflammation, infectious and cardiovascular diseases (8). A growing amount of evidence has indicated that Evo exhibits anticancer activity against various types of cancer, such as tongue, colon and breast cancer (9)(10)(11)(12). According to studies, this activity of Evo may be mediated by NF-κB (9), transforming growth factor β1 (TGF-β1) (11) and/or the p53/p21/Rb pathway (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also showed that EVO would be a potential therapeutic drug against other diseases such as hypomotility disorders [ 25 ], renal tubulointerstitial fibrosis [ 26 ], and IgE-induced allergenic diseases (including rhinitis and atopic dermatitis) [ 27 ]. Recently, EVO was widely reported to have the potential to become a therapeutic medicine for treating various cancers [ 28 , 29 ] due to its ability to cause tumor cell apoptosis by suppressing the NF-κB activity on tongue cancers both in vitro and in vivo [ 30 ]. A famous pill called Zuojin Pills, containing EVO, could be used for hepatocellular carcinoma treatment [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that TRAIL induces apoptosis in cancer cells but simultaneously activates NF-ĸB (32)(33)(34)(35)(36). Additionally, we showed that several chemotherapeutic agents activate NF-ĸB survival signaling (37) and agents, including nitric oxide-donors, that inhibit NF-ĸB can potentiate anti-tumor activity (37)(38)(39). NO has been to shown to sensitize TRAILresistant tumors to TRAIL via inhibition of NF-kB (40,41).…”
mentioning
confidence: 97%